2020
DOI: 10.1093/rheumatology/keaa076
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up results of myositis patients treated with H. P. Acthar gel

Abstract: Objectives Idiopathic inflammatory myopathies (IIM) are a group of autoimmune diseases characterized by proximal muscle weakness. H. P. Acthar gel [repository corticotropin injection (RCI)] is a formulation of adrenocorticotropic hormone and has been approved by Food and Drug Administration for use in IIM; however, literature is limited. In this study, we report longitudinal follow-up of myositis patients treated with RCI. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, patients who discontinued RCI after 6 months of clinical efficacy experienced a slow increase in disease activity and disability index and a decrease in muscle strength; their first flare occurred 4 months after discontinuation of RCI. 25 Interim results from an open-label study of RCI in 9 adults with refractory cutaneous DM reported that at 3 months, 7 patients had improved Cutaneous Dermatomyositis Disease Area and Severity Index activity scores and 8 patients had improved Physician Global Assessment activity scores. 26 The current study is limited by its retrospective design and the small sample size yielded by our recruitment efforts.…”
Section: Safetymentioning
confidence: 99%
“…In addition, patients who discontinued RCI after 6 months of clinical efficacy experienced a slow increase in disease activity and disability index and a decrease in muscle strength; their first flare occurred 4 months after discontinuation of RCI. 25 Interim results from an open-label study of RCI in 9 adults with refractory cutaneous DM reported that at 3 months, 7 patients had improved Cutaneous Dermatomyositis Disease Area and Severity Index activity scores and 8 patients had improved Physician Global Assessment activity scores. 26 The current study is limited by its retrospective design and the small sample size yielded by our recruitment efforts.…”
Section: Safetymentioning
confidence: 99%
“…Furthermore, corticotropin gel treatment was also less likely to contribute to severe steroid-related adverse events in comparison to glucocorticoid treatment, while still providing anti-inflammatory benefits. [ 46 ]…”
Section: Anti-inflammatory Therapiesmentioning
confidence: 99%
“…RCI is distinct from corticosteroids, inhibitors of cell activation, proliferation, and migration (e.g., methotrexate, azathioprine, leflunomide, mycophenolate), TNF-a antagonists (e.g., adalimumab, infliximab), and anti-cluster of differentiation (CD)20 antibodies (i.e., rituximab) [56,58,59]. In other inflammatory conditions, such as systemic lupus erythematosus, idiopathic inflammatory myopathies, and rheumatoid arthritis, RCI has been found to be safe and effective for treatment of patients who were nonresponsive to corticosteroids [60][61][62]. The effectiveness of RCI in patients who are refractory to corticosteroids supports RCI's unique mechanism of action that is distinct from steroids.…”
Section: Therapeutic Options For Pulmonary Sarcoidosismentioning
confidence: 99%